Citotoxicidade de complexos de rutênio contendo aminoácidos sulfurados em células tumorais - Leite, Celisnolia Morais (2016)
The work presents the synthesis and characterization of three new ruthenium II complexes containing sulfur amino acids, to evaluate the probable influence of the amino acids on the complexes cytotoxic activity. The complexes were characterized by 31P, 1H and 13C NMR, infrared and UV-visible spectroscopies, cyclic voltammetry and differential pulse voltammetry, molar conductivity, elemental analysis, and monocrystal X-ray diffraction. The studies of lipophilicity showed Log P values for the compounds, within the limits indicated by the literature for good absorption. The reactivity study of the complexes showed that in compounds 1 and 2 there is an exchange of ligands when exposed to DMSO, generating several species in solution after the period of 48 h. While in compound 3 this exchange did not occur. In the interaction studies of the complexes with the DNA, results of spectrophotometric titration and viscosity were obtained, which indicated that the compounds interact weakly with the DNA, which may be electrostatic or between the grooves. In the study of the interaction of the complexes with the HSA, by spectrofluorimetric titration, the compounds showed a binding constant (Kb) of the order of 104, which indicated that the compounds interact with the HSA, with the mechanism of static interaction and the involved forces, are hydrophobic forces. The cytotoxicity of the complexes also evaluated against breast cancer cell lines (MDA-MB-231 and MCF-7) and a non-tumor cell, V79 (Chinese hamster fibroblasts), in which the compounds were active. The complex 2 stood out for presenting a selectivity index good (3.79) about the triple-negative breast tumor line (MDA-MB-231). Therefore, the results obtained in this study were relevant to contribute to the generation of knowledge about the importance of amino acids in the planning of new compounds as potential antitumor agents